Immune dysregulation among students exposed to exam stress and its mitigation by mindfulness training: findings from an exploratory randomised trial - Turner, Lorinda; Galante, Julieta; Vainre, Maris; Stochl, Jan; Dufour, Géraldine; Jones, Peter B (Scientific reports, 2020)
Psychological distress persisting for weeks or more promotes pro-inflammatory immune dysregulation, a risk factor for a range of chronic diseases. We have recently shown that mindfulness training reduces distress among university students. Here we present an exploratory trial to study immune dysregulation in a cohort of students who were exposed to progressively greater stress as the exam period approached, and to explore whether mindfulness training mitigated this dysregulation. Healthy University of Cambridge students were randomised to join an 8-week mindfulness course (N = 27), or to mental health support as usual (N = 27). Psychological distress, immune cell proportions, cytokines, CRP and serum cortisol were measured at baseline and during the exam period. Increased distress was associated with statistically significant increases in the proportion of B cells, regardless of trial arm (*p = 0.027). There were no other associations between any of the measured parameters, distress or mindfulness. Our finding that the proportion of B cells increases with psychological distress supports the findings of other studies. However, we found no evidence that mindfulness training is able to buffer the effects of psychological distress on healthy participants' immune system. In order to detect these effects, should they exist, larger randomised trials will be required.
Keywords: dospělí; imunitní systém; Female; Cytokines; Adult; Immune System; mladý dospělý; ženské pohlaví; psychický stres; hydrokortison; Adolescent; cytokiny; lidé; Hydrocortisone; Students, Medical; všímavost; kohortové studie; studenti lékařství; Cohort Studies; Mindfulness; Stress, Psychological; Young Adult; B-Lymphocytes; B-lymfocyty; duševní zdraví; Mental Health; mladiství; Humans